Contemporary Terminological Problems in a Cross-linguistic Perspective - N. K. Riabtseva (Научный диалог)
The paper focuses on terminological problems in contemporary cross-linguistic communication that are generated primarily by two main tendencies in global scientific communication — the digitalization in information processing and the English language globalization. Both are closely connected with a new approach in linguistics — discourse clustering and its role in promoting foreign language and translation instruction. The paper provides a corpus-based account of Russian–English translation problems concerning clear-cut distinctions between Russian versus English academic style’s language-specific patterns in terminology discursive clustering, as well as their didactic and methodological importance for foreign language acquisition, Russian-English and English-Russian translation. The main idea is that the most important contemporary terminological problem in a cross-linguistic perspective is the lack of active authentic and language-specific terminology patterns in Russian–English scientific translations.